Diversidade e evolução de metaloproteases da peçonha da aranha Loxosceles laeta peruana revelada por análise transcriptômica - Raíssa Medina Santos (2018)
Spiders of the genus Loxosceles express in their venom glands various toxins, such as Phospholipases D, responsible for most of the symptoms caused by Loxoscelism and Metalloproteases, which may be involved in the hemorrhagic actions and the dissemination of venom. Several studies have shown that the cutaneous-visceral cases, the most severe form of Loxoscelism, are mainly caused by the Loxosceles laeta spider, which is found in several countries of South America, such as Brazil, Peru and Chile. In addition, there are almost three times as many bite-related deaths from L. laeta in Peru compared to Brazil. Thus, the present study aimed to perform an analysis of the transcripts of the venom gland of the Peruvian L. laeta species by bioinformatic tools with a focus on metalloproteases, because they did not have their fully identified functions, in order to describe and characterize them, investigating intraspecific differences of poisons that may justify the high severity of Peruvian accidents. Nine metalloproteases from the L. laeta venom from Peru were described and these results were validated by in silico and in vitro experiments comparing them with the metalloproteases from the Brazilian lax Loxosceles venom. The results demonstrated important differences between the Peruvian metalloprotease sequences with all other metalloproteases of Loxosceles species as well as their in vitro activity. These preliminary data indicate that further investigation of the action of these enzymes on the loxoscelic venom may contribute to a better understanding of the poisoning caused by these spiders.